دراسة تحليلية لبعض مؤشرات النمو في الفول تحت تأثير الري التكميلي - عبد العزيز, محمد; محمد, يوسف (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث في مزرعة كلية الزراعة في جامعة تشرين، لدراسة تأثير الري التكميلي في بعض مؤشرات النمو الفيزيولوجي للفول العادي (الصنف المالطي). استخدمت ثلاث معاملات للري (شاهد يعتمد على الأمطار فقط، ومعاملة أمطار + رية واحدة، ومعاملة أمطار + ريتين). صممت التجربة بطريقة القطاعات العشوائية الكاملة في ثلاثة مكررات. بينت الدراسة النتائج الآتية: أعطى الري التكميلي مرة ومرتين زيادة معنوية في المسطح الورقي، ودليل المساحة الورقية، والمساحة النسبية للأوراق، وفترة بقاء الأوراق على كفاءتها والكفاءة التمثيلية والمحصول الاقتصادي بالمقارنة مع الشاهد خلال مراحل النمو بعد 42، 84 و126 يوماً. تفوقت معاملة الري مرتين معنوياً على معاملة الري مرة واحدة في جميع مؤشرات النمو المذكورة أعلاه. قدرت الزيادة بعد 84 يوماً 7.35% من المسطح الورقي، و11.44% في دليل المساحة الورقية، و5.58% في المساحة النسبية للأوراق، و8.58% في معدل النمو النسبي للورقة، و3.27% في معدل النمو المحصولي، و18.60% في معدل النمو النسبي، و8.95% في فترة بقاء الأوراق على كفاءتها، و17.39% في الكفاءة التمثيلية و32.03% في المحصول الاقتصادي. The research was carried out in the farm of the Faculty of Agriculture, Tishreen University, in order to study the effect of supplementary irrigation on some physiological growth parameters in the Malta variety of faba bean. Three irrigation treatments were used. The first depends on rainfall; the second was applied when no rainfall occurred; and the third included two irrigations. The test was completely randomized with three replications. The result showed that the adding of one-time and two-time supplementing irrigations significantly increased leaf area (LA), leaf area index (LAR), leaf area ratio (LAR), relative leaf growth rate (RLGR), relative growth rate (RGR), crop growth rate (CGR), leaf area duration (LAD), net assimilation rate (NAR) and economic yield (EY) in comparison to the control during the growth stages after 42, 84, and 126 days. The two-time irrigation significantly surpassed the one-time irrigation in all growth parameters mentioned above. The increase reached after 84 days was 7.35 % in LA, 11.44 % in (LAI), 5.58 % in (LAR), 8.58 % in (RLGR), 3.27 % in (CGR), 18.60 % in (RGR), 8.95 % in (LAD), 17.39 % in (NAR) and 32.03 in (EY).